The 'Baby Dolls' : Breaking the Race and Gender Barriers of the New Orleans Mardi Gras Tradition - Vaz, Kim Marie (Book collections on Project MUSE., 2013)
"One of the first women's organizations to mask and perform during Mardi Gras, the Million Dollar Baby Dolls redefined the New Orleans carnival tradition. Tracing their origins from Storyville-era brothels and dance halls to their re-emergence in post-Katrina New Orleans, author Kim Marie Vaz uncovers the fascinating history of the 'raddy-walking, shake-dancing, cigar-smoking, money-flinging' ladies who strutted their way into a predominantly male establishment. The Baby Dolls formed around 1912 as an organization of African American women who used their profits from working in New Orleans's red-light district to compete with other Black prostitutes on Mardi Gras. Part of this event involved the tradition of masking, in which carnival groups create a collective identity through costuming. Their baby doll costumes--short satin dresses, stockings with garters, and bonnets--set against a bold and provocative public behavior not only exploited stereotypes but also empowered and made visible an otherwise marginalized female demographic. Over time, different neighborhoods adopted the Baby Doll tradition, stirring the creative imagination of Black women and men across New Orleans, from the downtown Treme area to the uptown community of Mahalia Jackson. Vaz follows the Baby Doll phenomenon through one hundred years with photos, articles, and interviews and concludes with the birth of contemporary groups, emphasizing these organizations' crucial contribution to Louisiana's cultural history."--Page 4 of cover.